WADAH KOMUNITAS SEPEDA MOTOR DI KOTAMATSUM III - MEDAN - Erwin Andrianto; Rudy Trisno (Jurusan Arsitektur dan Perencanaan, 2020)
In this study aims to discuss about the third place in the motorcycle community at Kotamatsum III in the city of Medan. The purpose of this study is to propose a design urban planning in the form of both physical and non-physical needs needed in the Kotamatsum III area of Medan by designing a motorcycle community place in the area, as a suitable third place in accordance with the program that has been prepared and to support the Masjid Raya Al-Mashun area as a place of worship and tourism that is comfortable, safe and creative, which is realized in the design of architectural designs that benefit all parties and on target. Third place as a public space in a neutral place, where people can gather and interact. Unlike the first place (home) and the second place (work), the third place allows people to put aside their worries and just enjoy the company and the conversation around them. The third place “holds individual, regular, voluntary, informal meetings and are happily anticipated outside the realm of home and work.”. These spaces promote social justice by enhancing guest status, providing background for grassroots politics, creating public association habits, and offering psychological support to individuals and society. The design methods used in this study are the concept of a metaphor. Second function follows form. The results of the study produce designs that are expected to meet the needs of the motorcycle community in the area both in design, function and program. AbstrakPenelitian ini bertujuan untuk menulusuri tentang tempat ketiga, dimana merupakan lingkungan sosial yang terpisah dari dua lingkungan sosial lainnya. Penelitian ini membahas tentang tempat ketiga yakni wadah komunitas motor di kawasan Kotamatsum III di kota Medan. Tujuan dalam penelitian ini adalah untuk memberikan usul perencanaan urban desain berupa kebutuhan–kebutuhan fisik maupun non fisik yang diperlukan pada kawasan Kotamatsum III – Medan, sebagai tempat ketiga yang layak sesuai dengan program yang telah disusun serta untuk mendukung kawasan Mesjid Raya Al – Mashun sebagai tempat ibadah dan parawisata yang nyaman, aman dan rekreatif yang diwujudkan dalam perancangan desain arsitektur yang menguntungkan semua pihak dan tepat sasaran. Tempat ketiga sebagai ruang publik di tempat netral, tempat orang dapat berkumpul dan berinteraksi. Berbeda dengan tempat pertama (rumah) dan tempat kedua (bekerja), tempat ketiga memungkinkan orang untuk mengesampingkan kekhawatiran mereka dan hanya menikmati suasana dan percakapan di sekitar mereka. Tempat ketiga